Etiology of retinal detachment and comparison of visual outcome after pars plana vitrectomy and scleral buckling surgical procedures - Nimra Ameen; Tanzila Rehman; Maryam Riaz; Sahibzadi Saira Saleem; Ali Ahmed Al-Halani; Anam Mehmood; Asma Saleem (BMC Ophthalmology)
Abstract Purpose The study is based on finding better treatment options and diagnostic methods for the particular type of retinal detachment (RD). Methods A cross-sectional comparative study was conducted at the Ophthalmology department of Holy Family Hospital, Rawalpindi from July 2023 to March 2024. Visual prognosis after surgery was calculated on the basis of a comparison of pre-operative and post-operative visual acuity. A total of 88 patients of both genders irrespective of age were included through consecutive non-random sampling techniques. Different diagnostic procedures were performed to evaluate the cause of Retinal Detachment. Pre-operative and Post-operative visual acuity was noted in comparison of two different surgical procedures. Results Among 88 patients 60% were males and 40% were females. According to the different causes of RD, RD with PDR (40%), RD with pseudophakia (20%), RD with Proliferative vitreoretinopathy (17%), RD with trauma (13%), RD with myopic degenerations (10%) were included. Visual acuity after surgery improved in 61 subjects, 35 patients with pars plana vitrectomy with silicon (PPV + SO) procedure and 26 patients with scleral buckling + cryotherapy (SB + Cryo) procedure and remained unchanged in 27 subjects, 9 with PPV + SO procedure and 18 with SB + Cryo procedure. There was a significant difference between the visual acuity of patients with PPV + SO and SB + Cryo surgical procedures, p < 0.05. Conclusions The main cause or risk factor of retinal detachment or tear/hole and the type of RD were found. There is a significant difference in the Visual acuity of the patients following PPV + SO and SB + Cryo surgery.